Progressivity of the Output Based Aid Voucher Programme and its Effects on Family Planning and Maternal Health in Nairobi and Kiambu Counties, Kenya - Ogo, Isaac Odeyovwi; Kioko, Urbanus M. (European Scientific Journal, ESJ, 2020)
Introduction: In developing countries, the poor and vulnerable are unable to access basic healthcare needs due to health financing related constraints. Healthcare needs are mostly financed through out of pocket, resulting in catastrophic expenditure. In 2006, the government of Kenya in partnership with Kfw implemented the Output-Based Aid (OBA) voucher programme to increase access for family planning and birth delivery in four counties in Kenya. However, evidence on the progressivity of the Output Based Aid voucher and its impact on FP and maternal healthcare services in Kenya is limited. The objective of this study was to examine progressivity of the OBA voucher programme and its effect on Long Term Family Planning methods and maternal health in Nairobi and Kiambu Counties of Kenya. The study adopted a case study research design, using data obtained from Kenya Ministry of Health (MOH).The Benefit Incidence Analysis (BIA) and binary probit regression model was used to analyse progressivity of the OBA voucher programme and its effect on Family Planning and Maternal Health. The findings showed that the OBA voucher programme was regressive because it did not benefit poor women. However, the study revealed that the OBA voucher programme had a positive effect on the utilization of maternal health acrossthe two counties. Based on the findings, thisstudy can be used to inform the design and implementation of the UHC particularly by ensuring that financing of family planning and maternal health services is progressive.